2018
DOI: 10.1177/0042098018798760
|View full text |Cite
|
Sign up to set email alerts
|

Training, skill-upgrading and settlement intention of migrants: Evidence from China

Abstract: The massive rural-to-urban migration has been one of the most important features of China’s labour market in recent decades. The recent pattern of return migration and migrant wages has increased the costs of firms in urban areas and has negatively affected urbanisation. Therefore, it is important to understand the determinants of settlement intention of migrants. Using data from Rural Urban Migration in China (RUMiC), we find that migrants express higher settlement intention in a city after receiving training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Remarkably, few scholars have paid attention to the effect of human capital enhancement in encouraging local livelihoods to alleviate dependence on natural resources around PAs [ 29 , 30 , 31 , 32 ]. As an important method of improving human capital, skill training can fundamentally improve the income of local residents, as has been confirmed by numerous studies [ 33 , 34 , 35 , 36 , 37 , 38 ]. In the agricultural sector, for example, trained farmers make a modest gain in knowledge and professional skills, leading to reduced pesticide use [ 39 ], mitigation of human-wildlife conflicts [ 40 ], and increases in household income [ 41 ].…”
Section: Introductionmentioning
confidence: 87%
“…Remarkably, few scholars have paid attention to the effect of human capital enhancement in encouraging local livelihoods to alleviate dependence on natural resources around PAs [ 29 , 30 , 31 , 32 ]. As an important method of improving human capital, skill training can fundamentally improve the income of local residents, as has been confirmed by numerous studies [ 33 , 34 , 35 , 36 , 37 , 38 ]. In the agricultural sector, for example, trained farmers make a modest gain in knowledge and professional skills, leading to reduced pesticide use [ 39 ], mitigation of human-wildlife conflicts [ 40 ], and increases in household income [ 41 ].…”
Section: Introductionmentioning
confidence: 87%
“…Human capital is the reflection of an individual’s ability to integrate into society and affects the degree of social integration through integrating willingness ( Wang et al, 2018 ). Huang et al (2018) found that rural women could increase their income by more than 98% after higher education.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…At present, the Chinese government implements a people-oriented urbanization strategy by expanding the supply of security housing in urban areas in order to increase the urbanization rate to 65% by 2025. The determinants of the attraction of migrants are important and have been extensively examined in the literature [ 10 , 11 , 12 , 13 , 14 ]. Moreover, a significant issue for the settlement intentions of migrants involves housing conditions and living costs [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%